Modern markers for the assessment of biological age - Dudek, Alicja; Zgliczyński, Wojciech (Wiedza Medyczna, 2023)
The steady increase in human life expectancy in the 21st century is considered one of the major public health challenges. However, current achievements in longevity, are most often associated with increasing years in disability. Current studies indicate that healthy longevity is achieved, through harmonised ageing of the whole body. Due to the complexity of ageing, a number of biological age markers have been determined to describe the intensity of changes limiting biophysiological functions at different levels of the body. Biological age markers can be divided into two categories: parameters determining the level of severity of molecular and cellular hallmarks of ageing: genomic incapacity, telomere length changes, mitochondrial dysfunction, loss of proteostasis, epigenetic changes, cellular senescence, deregulation of nutrient sensitivity, stem cell depletion, altered intercellular communication. The second group are parameters defining age at the systemic level: bone age, muscle age, vascular age, neuronal age, endocrine age, pulmonary age, glycan age. Modern methods of measuring biological age markers allow the identification of weak points in ageing and illustrate the unevenness of the ageing process. It is worth considering the study of biological age markers to prioritise interventions promoting sustainable ageing.